Analyze Children’s Scientific Literacy Skills in Relation to Covid-19 Through Story Telling Method in RA An-Najmush Saghir, Gorontalo - Sitti Rahmawati Talango; Nuryati Nuryati; Muthmainnah Muthmainnah (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
The covid-19 pandemic is a natural and social phenomenon that is happening, and causes unrest with high mortality data in Indonesia, as well as around the world. The spread of plague through local transmission, became the reason for the formation of home learning programs as a new habitual pattern in learning. In its implementation, home learning programs form children's understanding of the current condition, namely covid-19 as a natural and social phenomenon. Science literacy is part of an individual's ability to understand natural and social phenomena around. Science literacy is part of an individual's ability to understand natural and social phenomena around. Science literacy skills can help children make scientifically informed decisions, especially in the face of the current pandemic situation. Through the method of telling children's science literacy skills around the covid-19 pandemic can be observed, based on three aspects, namely; aspects of context, knowledge and competence. The results of observational analysis of storytelling methods applied by teachers in group B RA An-Najmush Saghir Gorontalo City, showed the average ability of children's understanding related to context aspects is 94.07% based on observed verbal and visual responses, then aspects of knowledge of the average ability of children 69.2%, observed through reasoning children after processing the covid-19 information scheme obtained through various sources as well as aspects of ability competency observed through response responses, children's questions in parse information related to covid-19 on average reached 89.63%.